Member of the organization - Antoniou, Klitsa (My University, 2026)
Evelyn Anastasiou: Rejected Sounds of the Magic Flute Presentation: Saturday, 30th of October 2021, 19:00 In the Garden of the Municipal University Library Coordinated and Produced by Cut Contemporary Fine Arts Lab and Klitsa Antoniou Curated by Konstantinos Argianas Conductor Dr. Francis Guy With the participation of The Commandaria Orchestra of the Cyprus Wine Museum in Limassol